Selected adjuvants increase the efficacy of foliar biofortification of iodine in bread wheat (Triticum aestivum L.) grain - Magor, Esther; Wilson, Matthew Deas; Wong, Henri; Cresswell, Tom; Sánchez-Palacios, José Tonatiuh; Bell, Richard William; Penrose, Beth (Frontiers in Plant Science, 2023)
Agronomic biofortification of crops is a promising approach that can improve the nutritional value of staple foods by alleviating dietary micronutrient deficiencies. Iodine deficiency is prevalent in many countries, including Australia, but it is not clear what foliar application strategies will be effective for iodine fortification of grain. This study hypothesised that combining adjuvants with iodine in foliar sprays would improve iodine penetration in wheat, leading to more efficient biofortification of grains. The glasshouse experiment included a total of nine treatments, including three reference controls: 1) Water; 2) potassium iodate (KIO3) and 3) potassium chloride (KCl); and a series of six different non-ionic surfactant or oil-based adjuvants: 4) KIO3 + BS1000; 5) KIO3 + Pulse® Penetrant; 6) KIO3 + Uptake®; 7) KIO3 + Hot-Up®; 8) KIO3 + Hasten® and 9) KIO3 + Synerterol® Horti Oil. Wheat was treated at heading, and again during the early milk growth stage. Adding the organosilicon-based adjuvant (Pulse®) to the spray formulation resulted in a significant increase in grain loading of iodine to 1269 µg/kg compared to the non-adjuvant KIO3 control at 231µg/kg, and the water and KCl controls (both 51µg/kg). The second most effective adjuvant was Synerterol® Horti Oil, which increased grain iodine significantly to 450µg/kg. The Uptake®, BS1000, Hasten®, and Hot-Up® adjuvants did not affect grain iodine concentrations relative to the KIO3 control. Importantly, iodine application and the subsequent increase in grain iodine had no significant effects on biomass production and grain yield relative to the controls. These results indicate that adjuvants can play an important role in agronomic biofortification practices, and organosilicon-based products have a great potential to enhance foliar penetration resulting in a higher translocation rate of foliar-applied iodine to grains, which is required to increase the iodine density of staple grains effectively.